The Subversive Nature of Inequality: Subjective Inequality Perceptions and Attitudes to Social Inequality - Andreas Kuhn (Center for Economic Studies and ifo Institute (CESifo), 2016)
This paper shows that higher levels of perceived wage inequality are associated with a weaker (stronger) belief into meritocratic (non-meritocratic) principles as being important in determining individual wages. This finding is robust to the use of an instrumental-variable estimation strategy which takes the potential issue of reverse causality into account, and it is further corroborated using various complementary measures of individuals' perception of the chances and risks associated with an unequal distribution of economic resources, such as their perception of the chances of upward mobility. I finally show that those individuals perceiving a high level of wage inequality also tend to be more supportive of redistributive policies and progressive taxation, and that they tend to favor the political left, suggesting a feedback effect of inequality perceptions into the political-economic sphere. Taken together, these findings suggest that high levels of perceived wage inequality have the potential to undermine the legitimacy of market outcomes.
Keywords: D31; D63; J31; 330; inequality perceptions; attitudes to social inequality; legitimacy of market outcomes; beliefs about the causes of economic success; support of redistribution; political preferences